Paradigma Posmodern Sebagai Dasar Filosofi Perilaku Budaya Masyarakat Indonesia di Masa Pandemi - Indra Tjahyadi; Jiphie Gilia Indriyani (SULUK: Jurnal Bahasa, Sastra, dan Budaya, 2021)
This paper focuses its study on the postmodern paradigm as the basis for the philosophy of cultural behavior of the Indonesian people during the COVID-19 Pandemic. This study aims to determine the relevance of the application of the postmodern paradigm as the basis for shaping and strengthening the national immunity of the Indonesian people. The approach used in this study is metodeliterature review. This approach is used because data collection and analysis is based on the literature study stage. The findings of this study are 1) the postmodern paradigm is a paradigm that appears as a critical reaction to the failure of modern projects, 2) rejection and denial of metanarations, monoliths, convention and arbitration systems, as well as rejection and denial of the objectification of truth, subject determination and limitation of freedom. are elements contained in the postmodern paradigm, 3) the postmodern paradigm is relevant to be applied as the basis for the philosophy of Indonesian people's behavior during the COVID-19 pandemic because it can help strengthen national values in Indonesian society.